Hygroaster iguazuensis sp. nov. and a new continental record for Lentinus similis - Lechner, B.E. (2005)
Hygroaster iguazuensis is proposed as a new species and Lentinus similis is a new record for the Americas. Both fungi are fully described and illustrated.